Attitude Towards Euthanasia Among Health Care Professionals of a Tertiary Care Hospital in Nepal: A Descriptive Cross-sectional Study - Khadka, Anjan; Banmala, Sabin; Timilsina, Bibek; Sapkota, Suhail; Karki, Saurab (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: The deliberate termination of a life to end suffering is known as euthanasia. There have been discussions on legalizing euthanasia in Nepal among physicians and legislators, but nothing has come out of it yet. It is critical to consider the opinions of medical experts while making decisions on euthanasia. Therefore, the purpose of this study is to find the attitude towards euthanasia among health care professionals in Nepal. Methods: A descriptive cross-sectional study was conducted among consultants, medical officers, post-graduate residents, and interns of a tertiary care hospital from November 2021 to May 2022 after getting approval from Institutional Review Committee. The responses were collected from convenience sampling was used and the findings were presented in descriptive manner using mean and percentages. Results: Among 107 participants, 71% of them showed positive attitude towards euthanasia and only 22.4% reported that they will perform euthanasia on themselves if it is needed and approved at any point of time. Conclusions: The majority of the healthcare professionals at a tertiary care hospital in Nepal revealed the wide range of opinions on euthanasia. This highlighted the need of ethical discussion and consideration to mold policies and practices in accordance with patient-centered care, cultural sensitivity, and the ethical obligations of healthcare professionals.